IMPLEMENTATION OF THE TAJRIBI, BAYANI, BURHANI, AND 'IRFANI METHODS IN THE STUDY OF PHILOSOPHY OF ISLAMIC EDUCATION - Dalmi Iskandar Sultani; Syarifuddin; Amroeni Drajat; Salminawati (SENSEI RESEARCH CENTER, 2021)
Allah is the source of all knowledge in Islam, and the Qur'an explains that Allah is the educator or teacher who educates the Prophet, Muhammad. This study aims to describe how the four scientific methods are implemented: Tajribi (observation and experiment), Bayani (explanation/interpretation), Burhani (logic/logical), and 'irfani (intuition). The data collection method uses library data, with various materials as the basis, research tools in literature, books, ancient manuscripts, notes, history, documents. The study results explain that tajribi is used to research empirical fields. Bayani is used to research, develop religious knowledge, explore knowledge in the Qur'an and hadith. Philosophers use Burhani to study and understand objects in the non-physical realm. Meanwhile, 'irfani is applied to uncover and reveal the secrets of God in the realm of non-physical objects. The Islamic method never taints the soul, only experiments, testing using reasoning to achieve goals. Since the early days of Islamic progress, these four scientific methods have been practiced with the applicable rules for acquiring knowledge.